Incorporating Virtual Reality into clinical practice to develop social skills for children with autism spectrum disorder - Dr. M Arun Kumar, K Sri Raagavi Devi (South Eastern European Journal of Public Health, 2025)
Background: Individuals with Autism spectrum disorder (ASD) typically encounter challenges in areas such as socio-emotional reciprocity; non-verbal communicative behaviours; and forming, maintaining, and comprehending relationships. Recent research suggests that Virtual Reality (VR) may be more beneficial than conventional occupational therapy for certain purposes. VR provides a controlled artificial environment with auditory and visual inputs, making it a suitable platform for teaching and practicing social skills in children with ASD. Objectives: This study aimed to examine the impact of VR-based interventions on fostering social abilities among children diagnosed with ASD as a part of clinical treatment. Study Design: Quasi experimental study design was employed. Methods: This study used the Indian Scale for the Assessment of Autism (ISAA) for screening. Thirty ASD diagnosed children were split equally between the control and experimental groups. The experimental group received a VR-based intervention for 36 sessions, 35 minutes per session, whereas the control group underwent conventional occupational therapy (OT) such as sensory integration, group therapy, social skills training and play therapy. The Autism Social Skills Profile-2 (ASSP-2) was administered pre- and post-intervention to evaluate socio-emotional reciprocity (SER), social participation avoidance (SPA), and detrimental social behaviour (DSB). Results: The results from the Mann Whitney U test revealed that the social skills scores on the ASSP-2 showed significant improvement after VR intervention in experimental group, compared to conventional OT (P=0.037, 95% confidence interval [CI] = -7.347, 0.787). Conclusion: The substantial improvement in the experimental cohort suggests that VR-based therapy enhances social skills in children on the autism spectrum, offering significant insights into existing research and advocating for its integration into clinical practice by occupational therapists.